STRATEGI PENGELOLAAN BEASISWA KIP DALAM PERSPEKTIF MANAJEMEN KEBIJAKAN PENDIDIKAN DAN DAMPAKNYA TERHADAP MOTIVASI BELAJAR MAHASISWA UIN RADEN MAS SAID SURAKARTA - Novita Sari, Aprillia; Atul Luthfiyah, Imro; Nur Hidayat, Farid (Penerbit Lafadz Jaya, 2026)
This study examines the management strategies of the KIP Kuliah Scholarship and their impact on learning motivation among students at UIN Raden Mas Said Surakarta, focusing on underprivileged recipients through a policy management approach. The objective is to analyze the influence of POAC management functions (planning, organizing, actuating, controlling) on student motivation. Employing a quantitative descriptive method, data were collected via online questionnaires from a population of 500 KIP recipients, with a sample of 83 students selected through cluster random sampling and Slovin's formula at a 10% error level. Instruments included Likert-scale questionnaires, analyzed using multiple linear regression in SPSS version 25, preceded by classical assumption tests. Results show all POAC functions positively and significantly affect motivation both partially (planning β=0.388, p=0.000; organizing β=0.182, p=0.018; actuating β=0.172, p=0.036; controlling β=0.382, p=0.000) and simultaneously (F=407.051, p=0.000), explaining 95.4% variance (Adjusted R²=0.954). In conclusion, effective POAC implementation enhances scholarship management, boosting intrinsic motivation and academic persistence among recipients.